(untitled) (Research, Society and Development, 2024)
The presence of a multidisciplinary team is crucial for fostering comprehensive mental well-being in full-day schools. This article highlights the significance of collaboration among diverse professions to address various aspects of students’ mental health. Optometry, psychology, occupational therapy, physical education, and nutrition are pivotal in promoting a holistic approach to mental health. Optometrists contribute by assessing visual health, recognizing the impact of unaddressed visual issues on academic performance and mental health. Psychologists focus on emotional assessments and interventions, empowering students to navigate stress and anxiety through coping skills and resilience building. Occupational therapists engage students in activities that enhance socioemotional skills and foster a sense of accomplishment. Physical education instructors and nutritionists promote healthy lifestyle habits, with regular physical activity and a balanced diet integral to students’ mental well-being, influencing mood and concentration positively. The collaboration of these disciplines forms a comprehensive support system, where optometry addresses visual health, psychology addresses emotional health, occupational therapy enhances practical skills, and physical education and nutrition cultivate healthy lifestyles. This integrated approach underscores the interconnectedness of these professions and their collective impact on students’ overall mental health and academic success. By adopting a multidisciplinary strategy, educational institutions can create an environment that prioritizes mental well-being, nurturing students who are not only academically proficient but also mentally resilient and empowered. This paper emphasizes that a holistic approach involving various health and educational professionals is essential in creating supportive and effective learning environments in full-day schools.